Role of minimally invasive glaucoma surgery in the management of chronic open-angle glaucoma - Ojasvi Sharma (Nature Portfolio, 2021)
Abstract To compare the safety and efficacy of phacoemulsification combined with ab-interno trabeculectomy (Trabectome) and phacoemulsification combined with I-Stent inject in patients with medically uncontrolled primary open-angle glaucoma (POAG). A retrospective comparative case series. 70 eyes of 66 patients completed 2 years follow up after these treatments performed in 2017–2018. 35 eyes of 33 patients underwent combined Phaco-Trabectome (PT); and 35 eyes of 33 patients underwent combined Phaco-I-Stent inject (Pi). Patient demographics and preoperative characteristics are comparable. A 20% drop in IOP was achieved in 27 eyes (77.14%) in PT group and 28 eyes (80%) in Pi group (p = 0.77). Success rate (target IOP achieved and maintained for 2 years) in advance glaucoma was 25% in PT group and 30.7% in Pi group (p = 0.90). In mild to moderate glaucoma, success rate was 85.71% in PT group and 90% in Pi group (p = 0.67). There was no significant difference between two groups with regards to mean reduction in glaucoma medications and complication rates. Trabectome and I-Stent combined with phacoemulsification are equally efficacious and safe for treating patients with medically uncontrolled mild and moderate primary open-angle glaucoma (POAG). However, they are not an effective treatment for patients with advanced glaucoma.